Derivation of Painlevé type system with D(1) 4 affine Weyl group symmetry in a self-similarity limit - Aratyn, H.; Gomes, J. F. [UNESP]; Lobo, G. V. [UNESP]; Zimerman, A. H. [UNESP] (Centre pour la Communication Scientifique Directe (CCSD), 2023)
We show how the zero-curvature equations based on a loop algebra of D4 with a principal gradation reduce via self-similarity limit to a polynomial Hamiltonian system of coupled Painlevé III models with four canonical variables and D(1) 4 affine Weyl group symmetry.